PRODUCTION OF ANTIBACTERIAL AGENT FROM FUNGI ISOLATED FROM PHARMACEUTICAL SOIL SAMPLE BY FERMENTATION UNDER OPTIMIZED CONDITIONS - Bhardwaj, Anupama; Chaman, Sonia; Verma, Sangeeta (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study aimed to isolate fungi having antibacterial activity from pharmaceutical site soil sample and production of antibacterial agents by solid and submerged state fermentation under optimized conditions. Antibacterial activity of laboratory isolated and produced antibacterial agent was compared with other commercialized antibiotics to check the efficiency of laboratory produced antibacterial agent. Methods: For isolation and characterization of fungal isolates American Public Health Association standard was followed. Antibacterial activity was determined using disc diffusion and agar disc diffusion method. Results: On the basis of morphological and microscopic characteristics six fungal isolates belongs to four different genus species, i.e., Aspergillus sp. (F1, F2, F3), Penicillium sp. (F4), Rhizopus sp. (F5), and Fusarium sp. (F6), and they were tested against six bacterial isolates, i.e., Streptococcus sp. (B1), Bacillus sp. (B2), Staphylococcus sp. (B3), Bacillus sp. (B4), Bacillus sp. (B5), and Enterococcus sp. (B6). Except B4 all bacterial isolates growth were inhibited by fungal isolates. Under optimized conditions maximum zone of inhibition, i.e., 78 mm against B1 and B5 shown by F1 and F6 at 2% and 1% glucose concentration, respectively, at 10 pH. When comparison was made between commercialized antibiotics and lab produced antibacterial agents, it was observed lab produced antibacterial agent was more efficient in terms of zone of inhibition. Conclusion: Lab isolated and produced antibacterial agents were more efficient than commercialized antibiotics. This study demonstrated that lab isolated antibacterial agents isolated from six fungal isolates seems to be a stable and potent antibacterial and can be used as alternative to expensive commercialized antibiotics. Â 